Circular economy and sustainable practices adopted by family farmers - Magalhães, Marcos Ferreira de; Ramos, Heidy Rodriguez; Bezerra, Claudia Maria da Silva (Revista de Administração da UFSM, 2024)
Purpose: This study proposes a Systematic Literature Review (SLR) focusing on the Circular Economy (CE) and entrepreneurial family farming, investigating how the adoption of sustainable practices influences the incorporation of CE principles in this context. Furthermore, the study aims to map trends and gaps in the scientific literature on this intersection, highlighting the relevance of CE to foster more sustainable and efficient agricultural practices. Methodology: A qualitative study with a descriptive approach was prepared through a SLR of 49 articles collected in the Web of Science and Scopus databases, whose content analysis was supported by Rayyan and Atlas ti software. Findings: The thematic analysis revealed four categories of practices related to CE: (a) CE Practices in Entrepreneurship, emphasizing the role of entrepreneurship in promoting sustainable business models; (b) CE Practices in Agriculture, highlighting the implementation of sustainable agricultural systems, including organic production and effective waste management; (c) CE Practices in the Designer, contemplating the need to rethink the processes of design, production, and marketing of products; (d) Sustainable CE Practices, addressing the reorganization of business processes and partnerships to promote sustainability in circular business models. Originality: This SLR provides a comprehensive overview of CE-related practices in entrepreneurial family farming. The research emphasizes the relevance of entrepreneurial practices as drivers of sustainable business models in the convergence between CE and family farming, while identifying gaps in research and suggesting directions for future investigations.